Histologic and histomorphometric alterations in the cranial and caudal vaginal mucous membrane of HF cow during follicular and luteal phases of estrus cycle - HASANZADEH, S; AYEN, E; KHALILZADEH, O (The Indian Journal of Animal Sciences, 2014)
Histologic observation revealed that in the cranial region of the vaginal epithelium a surface layer of coiumhar cells are present at both the follicular and luteal phases. These cells were PAS reactive. The mast cells were distributed in all the layers of vagina, but their population were higher in luteal than the follicular phase. There were significant difference (P